Biaxially crumpled silver thin-film electrodes for dielectric elastomer actuators - Low, Sze-Hsien (2014)
Metal thin films, which have high conductivity, are much stiffer and may fracture at a much lower strain than dielectric elastomers. In order to fabricate compliant electrodes for use in dielectric elastomer actuators (DEAs), metal thin films have been formed into either zigzag patterns or corrugations, which favour bending and only allow uniaxial DEA deformations. However, biaxially compliant electrodes are desired in order to maximize generated forces of DEA. In this paper, we present crumpled metal thin-film electrodes that are biaxially compliant and have full area coverage over the dielectric elastomer. These crumpled metal thin-film electrodes are more stretchable than flat metal thin films; they remain conductive beyond 110% radial strain. Also, crumpling reduced the stiffening effect of metal thin films on the soft elastomer. As such, DEAs using crumpled metal thin-film electrodes managed to attain relatively high actuated area strains of up to 128% at 1.8 kV (102 V μm-1).